Flow and heat transfer investigation of a circular jet issuing on different types of surfaces - Bolek, Abdullah; Bayraktar, Seyfettin (SPRINGER INDIA, 2019)
In the present study, flow and heat transfer characteristics of an impinging jet issuing from a circular cross-sectional pipe on a rectangular plate, convex and concave hemispheres were investigated numerically for various Reynolds numbers and jet-to-plate distances. Steady and three-dimensional Reynolds-Averaged Navier-Stokes equations were solved iteratively utilizing finite volume method. Turbulence model assessment study reveals that the transitional Shear Stress Transport k-omega turbulence model can be used for such a problem. Regardless of the geometry of the impinging surfaces, two different flow regions were detected around y/D = 3. The first region starts from the stagnation point (y/D = 0) to the edge of the rectangular plate and hemispheres (y/D = 3). In this region, the maximum heat transfer is obtained for the jet impinging on the rectangular plate. However, in the second region that covers the wall jet zone the impinging jet on the convex hemisphere provides the maximum while the concave causes the minimum heat transfer. The most efficient jet-to-plate distance is found as H/D = 2 in the first region while heat transfer does not change with distance in the wall jet zone. It was shown that Nusselt number increases with Reynolds number when the jet impinges on the concave and convex hemispheres as observed for the impinging jet on a flat plate.
Keywords: Impinging jet; heat transfer; computational fluid dynamics; turbulence; convex surface; concave surface; WALL SHEAR-STRESS; IMPINGEMENT; CONCAVE; SIMULATION; DYNAMICS; MODELS; Engineering